PRODUCT INNOVATION AND MARKETING MANAGEMENT OF UMKM FOOD AND BEVERAGES AMID GLOBAL COMPETITION: SURABAYA CITY CASE STUDY - Abdulloh, Abdulloh; Sudarmiatin, Sudarmiatin; Wardana, Ludi Wishnu (PUSAT KEWIRAUSAHAAN UNIVERSITAS BALIKPAPAN, 2024)
This research aims to explore product innovation and marketing management in small and medium enterprises (MSMEs) in the food and beverage sector in Surabaya, which face the challenges of global competition. With the number of MSMEs in this field reaching around 12,000, Surabaya offers a vibrant ecosystem for analysis. The research method used includes a survey with questionnaires distributed to SMEs, to collect data on innovation strategies, marketing channels, and challenges faced in daily operations. The results showed that product innovation, especially in the aspects of developing new recipes and attractive packaging, contributed positively to increased sales. In addition, the application of social media as a marketing channel has proven effective in expanding market reach and improving brand image among consumers. However, many MSMEs still face significant challenges, such as limited resources and lack of support in research and development. Based on these findings, it is recommended that MSME players should be more active in involving consumers in the innovation process and utilize support from the government and related institutions. This research is expected to provide valuable insights for other MSME players in improving competitiveness and business sustainability in an increasingly competitive market.